Individual Attitudes Toward Corruption : Do Social Effects Matter? - Gatti, Roberta (World Bank, Washington, DC, 2014)
Using individual-level data for 35 countries, the authors investigate the microeconomic determinants of attitudes toward corruption. They find women, employed, less wealthy, and older individuals to be more averse to corruption. The authors also provide evidence that social effects play an important role in determining individual attitudes toward corruption, as these are robustly and significantly associated with the average level of tolerance of corruption in the region. This finding lends empirical support to theoretical models where corruption emerges in multiple equilibria and suggests that "big-push" policies might be particularly effective in combating corruption.